Floristics and ex situ germination of the soil seed bank under different light levels (Research, Society and Development, 2021)
Soil seed banks bring information about the current flora and allow future scenarios about plant communities. The objective of this work was to determine the percentage of ex situ germination of a seed bank under different levels of light. Sampling took place in primary a harvested primary forest under fallow in the municipality of Moju, Pará state, Brazil. Ten samples composed of four simple samples were collected in 10 plots of the topsoil (5 cm). The samples were maintained in a greenhouse and randomly distributed in Styrofoam trays under three light conditions: Shade (greenhouse + 70% shade net); Medium Shade (greenhouse + 30% shade net), and Full Sun, with five repetitions each. After 120 days, the seed bank presented 414 seedlings of 61 species, 48 genera, and 34 families. From this total, 27.78% of the individuals germinated in the three environments analyzed. The environment with the highest germination of individuals was Medium Shade (F = 140.25; p = 0.0001; CV = 3.60%), which also included 48.15% of the germinated species. The seed bank showed high floristic diversity with a predominance of tree, pioneer, and zoochoric species. In this way, environmental conditions determine the germination of the seed bank, with emphasis on the Medium Shade environment and the Fabaceae, Rubiaceae and Urticaceae families.